Problematika dan Solusi Masa Depan Hadis dan Ulumul Hadis - Muhammad Rusli; Nazar Husain HPW (AL-Fikr, 2013)
Along with the progress of time, some aspects of religious belief which previously considered to be final are now beginning to be questioned, including the aspect of hadith and Ulumul Hadith. This questioning should not be interpreted as a contravention to religious values. Rather, it should be regarded as a positive effort to advance a living religion. Among the problems of hadith and Ulumul Hadith which have always been questioned are the aspects of history, authority, authenticity, interpretation, methodology, capability of hadith to meet contemporary challenges and so forth. In response to this situation, solutions offered comprise: methods of isnad and matn analysis; thematic hadith assessment studies (maudu'iy), contextualization or re-interpretation of hadith meaning, reconstruction of Ulumul Hadith; and application of hermeneutic methods. Implementation of these techniques is expected to serve as answers to the problems facing Ulumul hadith and hadith, and also as stimulations to enforce the spirit of Islamic studies in general.